3D Two‐Photon Microprinting of Nanoporous Architectures. Issue 32 (30th June 2020) - Mayer, Frederik; Ryklin, Daniel; Wacker, Irene; Curticean, Ronald; Čalkovský, Martin; Niemeyer, Andreas; Dong, Zheqin; Levkin, Pavel A.; Gerthsen, Dagmar; Schröder, Rasmus R.; Wegener, Martin
Abstract: A photoresist system for 3D two‐photon microprinting is presented, which enables the printing of inherently nanoporous structures with mean pore sizes around 50 nm by means of self‐organization on the nanoscale. A phase separation between polymerizable and chemically inert photoresist components leads to the formation of 3D co‐continuous structures. Subsequent washing‐out of the unpolymerized phase reveals the porous polymer structures. To characterize the volume properties of the printed structures, scanning electron microscopy images are recorded from ultramicrotome sections. In addition, the light‐scattering properties of the 3D‐printed material are analyzed. By adjusting the printing parameters, the porosity can be controlled during 3D printing. As an application example, a functioning miniaturized Ulbricht light‐collection sphere is 3D printed and tested. Abstract : Combining self‐assembly on the nanoscale and two‐photon 3D laser printing on the micrometer scale, complex nanoporous 3D architectures are achieved. The underlying photoresist relies on polymerization‐induced phase separation between the polymer and a nonpolymerizable phase. Control of the porosity by the printing parameters is demonstrated by sample characterization based on ultramicrotomy, scanning electron microscopy, and optical transmission.